Development of new all-optical signal regeneration technique - Das, Bhagwan; Abdullah, Mohammad Faiz Liew; Mohd Shah, Nor Shahida; Adam Ahmed, Labeeb Mohammed; Pandey, Bishwajeet (Springer Netherlands, 2017)
All-optical signal regeneration have been the active research area since last decade due to evolution of nonlinear optical signal processing. Existing all-optical signal regeneration techniques are agitated in producing low Bit Error Rate (BER) of 10-10 at below than -10 dBm power received. In this paper, a new all-optical signal regeneration technique is developed by using phase sensitive amplification and designed optical phase locked signal mechanism. The developed all-optical signal regeneration technique is tested for different 10 Gb/s Differential Phase Shift Keying degraded signals. It is determined that the designed all-optical signal regeneration technique is able to provide signal regeneration with noise mitigation for degraded signals. It is analyzed that overall, for all degraded test signals, average BER of 10-13 is achieved at received power of -14 dBm. The designed technique will be helpful to enhance the performance of existing signal regeneration systems in the presence of severe noise by providing minimum BER at low received power.